(untitled) (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
In this article, based on memories of ex-conscript soldiers and documents from the period, we analyze how a “culture of terror” was created in the south of Tucumán during Ope- rativo Independencia (1975-1977). Especially, we will show how military power made use of a series of “psychological operation” tasks: the production and circulation of rumors about the rural guerillas’ dangerousness and a process of enemy construction where guerillas, activists and oppo- nents were transformed into “fuleros”, “extremists” or “ene- my”. Likewise, we will illustrate how ex-conscript soldiers, over thirty years later from the beginning of this repressive operation, seek to render intelligible the group of messages received during their conscription, hard and enigmatic core of this political repression experience.